Metabolic Changes in Scylla paramamosain During Adaptation to an Acute Decrease in Salinity - Yao, Hongzhi; Li, Xing; Chen, Yuhao; Liang, Guoling; Gao, Gao; Wang, Huan; Wang, Chunlin; Mu, Changkao (Frontiers in Marine Science, 2021)
The mud crab Scylla paramamosain is an important euryhaline mariculture species. However, acute decreases in salinity seriously impact its survival and can result in large production losses. In this study, we evaluated metabolic changes in S. paramamosain exposed to an acute salinity reduction from 23 psu to 3 psu. After the salinity decrease, hemolymph osmolality declined from 726.75 to 642.38 mOsm/kg H2O, which was close to the physiological equilibrium state. Activities of osmolality regulation-related enzymes in the gills, including Na+-K+-ATPase, CA, and V-ATPase all increased. Using LC-MS analysis, we identified 519 metabolites (mainly lipids). Additionally, 13 significant metabolic pathways (P < 0.05) were identified via enrichment analysis, which were mainly related to signal pathways, lipids, and transportation. Our correlation analysis, which combined LC-MS and previous GC-MS data, yielded 28 significant metabolic pathways. Amino acids and energy metabolism accounted for most of these pathways, and lipid metabolism pathways were insignificant. Our results showed that amino acids and energy metabolism were the dominant factors involved in the adaptation of S. paramamosain to acute salinity decrease, and lipid metabolites played a supporting role.